Ethnomathematics in Making Woven Fabrics in the Sipirok Community - Siregar, Ika Milia Wahyuni; Rakhmawati, Fibri (Universitas Islam Negeri Raden Intan Lampung, 2023)
Ethnomathematics is one method of learning mathematics that is expected to be another alternative that seeks to make students interested in learning mathematics. Besides being theoretical, ethnomathematics teaches how mathematics may be employed in real-world circumstances. This study aims to understand more about how mathematics is used in the production of traditional Sipirok woven fabrics. The author employed a qualitative research method in this study, and the data was gathered through observation, interviews, and recording. One of the weavers of Sipirok woven fabric provided the sample. According to the findings, there is mathematics in manufacturing Sipirok woven fabric, specifically in the loom used and woven fabric motif. Thus, ethnomathematics can support students' mathematics learning and aid in understanding the teacher's instruction. It is suggested that other researchers study Indonesian cultures that incorporate ethnomathematics, as many unexplored Indonesian cultures remain.